Wellen's T Waves and U Waves in Acute Coronary Syndrome - Lebehn, Mark (University Clinical, Education & Research Associate (UCERA), 2013)
INTRODUCTION: The most common electrocardiographic (EKG) finding suggestive of acute severe ischemia is development of the ST segment depression. Although this is the most sensitive EKG marker for transient ischemia, ST segment depression cannot reliably identify the location of the ischemia in most cases. In contrast, T wave inversion, especially so-called “ischemic T wave” is not as common as ST depression, however, it is more specific for location of the ischemia on the surface EKG. Wellen's Syndrome, ie, deeply and symmetrically inverted T wave in the anterior lead (Type A), and biphasic T wave with positive initial deflection and negative terminal deflection (Type B), has been well-known for identifying the presence of severe anterior ischemia due to proximal LAD stenosis. The development of U wave inversion in the precordial lead has also been noted to be a specific marker of the proximal LAD stenosis. We present a case of acute coronary syndrome (ACS) in a patient who demonstrates both EKG findings serially and who subsequently was found to have severe proximal LAD stenosis. CASE DESCRIPTION: A 52-year-old man with a 20 pack smoking history and hypertension presented with chest pain. He was initially noted to have inverted U waves in leads V(3) and V(4) which subsequently evolved into deep and symmetric T wave inversion in leads V(2) through V(4) on EKGs taken during chest pain free periods. Troponin I peaked at 1.11 ng/L. He was treated with standard ACS medications. Coronary angiography showed a subtotally occluded proximal LAD which was subsequently stented. He had an uneventful hospital course and was later discharged. DISCUSSION: Although described separately in literature, EKG changes seen in Wellen's Syndrome and the lesser-known inverted U wave can identify the high risk patient population with proximal LAD stenosis. We will review the literature regarding Wellen's Syndrome and inverted U wave and raise physician awareness in recognizing the implication of these EKG changes for instituting early therapy and providing timely intervention in these high-risk patients.